1997
DOI: 10.1007/s002469900169
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Cardiomyopathy: Molecular and Biochemical Analysis

Abstract: Abnormalities in cardiac mitochondrial respiratory enzymes and mitochondrial DNA have been found in an increasing number of pediatric cases of both dilated and hypertrophic cardiomyopathy, giving rise to the entity known as mitochondrial cardiomyopathy. Histochemical, biochemical, and molecular findings are described in this review of mitochondrial cardiomyopathy, which should provide assistance in its diagnostic identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 76 publications
0
20
0
1
Order By: Relevance
“…Because some organs, especially as skeletal muscle, central nervous system and heart, are highly dependent on the energy produced by mitochondrial oxidation, mitochondrial cardiomyopathy could be one of the common manifestations of mitochondrial diseases [1]. Abnormal oxidative phosphorylation has been reported to cause hypertrophic or dilated cardiomyopathy, and concentric hypertrophy seems to be most commonly associated with mitochondrial disease.…”
Section: Discussionmentioning
confidence: 99%
“…Because some organs, especially as skeletal muscle, central nervous system and heart, are highly dependent on the energy produced by mitochondrial oxidation, mitochondrial cardiomyopathy could be one of the common manifestations of mitochondrial diseases [1]. Abnormal oxidative phosphorylation has been reported to cause hypertrophic or dilated cardiomyopathy, and concentric hypertrophy seems to be most commonly associated with mitochondrial disease.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities of cardiac conduction are common, even among asymptomatic patients (68), and although they are a central feature of KSS they may occur in any MM. Cardiomyopathy may be hypertrophic or dilated and is most commonly present in MELAS, MERRF, and KSS (69). Figures are not available for adults, although one study in children demonstrated hypertrophic cardiomyopathy to be present in 17%, often asymptomatic, and associated with higher mortality than MM patients without cardiomyopathy (70).…”
Section: Treatmentmentioning
confidence: 99%
“…Multiple defects in different organs are common, and most vulnerable tissues include the nervous, muscle and cardiac tissues, of which cell types require high energy metabolism [12], [14]. Mitochondrial cardiomyopathy (MCM), a common manifestation of mitochondrial respiratory disorders, involves the development of cardiac hypertrophy and heart failure [16], [17]. The age of onset for MCM is variable, as it can be detected in infants, children or adults [16], [18].…”
Section: Introductionmentioning
confidence: 99%